Word embodied the jeweled pagoda mandalas in Japanese Buddhist art - O'Neal, Halle (Harvard East Asian monographs, 2018)
"Examines the Japanese Buddhist jeweled pagoda mandala paintings, unpacking their revolutionary use of text as picture to show how this visual conflation mirrors important conceptual indivisibilities in medieval Japan. The textual pagoda projects the complex constellation of relics, reliquaries, scripture, and body in religious doctrine, praxis, and art"--Provided by publisher.